Long-term postural control in elite athletes following mild traumatic brain injury - Al-Husseini, Ali; Gard, Anna; Fransson, Per-Anders; Tegner, Yelverton; Magnusson, Måns; Marklund, Niklas; Tjernström, Fredrik (Frontiers in Neurology, 2022)
Background: Trauma to the head and neck are common in sports and often affects otherwise healthy young individuals. A sport-related concussions (SRC), defined as a mild traumatic brain injury (mTBI), may inflict persistent neck and shoulder pain, and headache, but also more complex symptoms such as imbalance, dizziness, and visual disturbances. These more complex symptoms may be difficulty to identify with standard health care diagnostic procedures. Objective: To investigate postural control in a group of former elite athletes with persistent post-concussive symptoms (PPCS) at least 6 months after the incident. Method: Postural control was examined using posturography during quiet stance and randomized balance perturbations with eyes open and eyes closed. Randomized balance perturbations were used to examine motor learning through sensorimotor adaptation. Force platform recordings were converted to reflect the energy used to maintain balance, and spectrally categorized into total energy used, energy used for smooth corrective changes of posture (i.e., <0.1 Hz) and energy used for fast corrective movements to maintain balance (i.e., >0.1 Hz). Results: The mTBI group included 20 (13 males, mean age 26.6 years) elite athletes with PPCS and the control group included 12 athletes (9 males, mean age 26.4 years) with no history of SRC. The mTBI group used significantly more energy during balance perturbations than controls: +143% total energy, p=0.004; +122% low frequency energy, p=0.007; and +162% high frequency energy, p=0.004. The mTBI subjects also adapted less to the balance perturbations than controls in total (18% mTBI vs 37% controls, p=0.042), low frequency (24% mTBI vs 42% controls, p=0.046) and high frequency (6% mTBI vs 28% controls, p=0.040). The mTBI subjects used significantly more energy during quiet stance than controls: +128% total energy, p=0.034; +136% low frequency energy, p=0.048; and +109% high frequency energy, p=0.015. Conclusion: Athletes with previous mTBI and PPCS used more energy to stand compared to controls during balance perturbations and quiet stance and had diminished sensorimotor adaptation. Sports-related concussions appear able to affect postural control and motor learning.